2017
DOI: 10.18203/2349-2902.isj20175887
|View full text |Cite
|
Sign up to set email alerts
|

Role of staple line fixation during laparoscopic sleeve gastrectomy

Abstract: Background: Although sleeve gastrectomy provides a technically simple procedure with minimal effect on digestive tract it deprives the stomach of its ligaments of fixation which results in impairment of gastric functions, vomiting, axial gastric rotation in addition to bleeding or leakage from the stable line. Objective of present study is the effect of stable line fixation during sleeve gastrectomy.Methods: This is a prospective randomized study using closed envelop method carried on 100 patients with morbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the literature, in a small number of studies evaluating the effects of SLR-O during LSG, similar to our findings, leakage, bleeding, and twist rates were found to be low (Table 4). [21][22][23][24] Afaneh et al's 25 study found that there was no significant difference between the omentopexy and standard LSG groups in the number of postoperative clinic visits, office telephone encounters, total postoperative readmissions, or postoperative readmissions associated with gastrointestinal symptoms such as nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, in a small number of studies evaluating the effects of SLR-O during LSG, similar to our findings, leakage, bleeding, and twist rates were found to be low (Table 4). [21][22][23][24] Afaneh et al's 25 study found that there was no significant difference between the omentopexy and standard LSG groups in the number of postoperative clinic visits, office telephone encounters, total postoperative readmissions, or postoperative readmissions associated with gastrointestinal symptoms such as nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…22,29,36 Various theories about how OP/GP prevents sleeve torsion are briefly reviewed here. According to Elbalshy's 2018 study, 37 the cause of spiral or twisted gastric sleeve might be the progressive rotation of the staple line in an anterior to posterior plane. The reason behind gastric sleeve twist/torsion is likely that the gastrosplenic and gastrocolic ligaments that fix the posterior wall of the stomach are cut, and the new stomach becomes mobile.…”
Section: Gastric Twist/torsionmentioning
confidence: 99%
“…The overall mortality rate was 0.3%. The most common mortality was due to pulmonary embolism, cardiopulmonary failure and gastric fistula (5).…”
Section: Introductionmentioning
confidence: 99%